2020
DOI: 10.1038/s41588-020-0595-4
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation disruption reshapes the hematopoietic differentiation landscape

Abstract: Mutations in genes involved in DNA methylation (DNAme; e.g., TET2, DNMT3A) , are frequently observed in hematological malignancies 1 – 3 and clonal hematopoiesis 4 , 5 . Applying single-cell sequencing to murine hematopoietic stem and progenitor cells, we observed that these mutations disrupt hematopoietic differentiation, causing opposite shifts in the frequencies of erythroid vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
176
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(204 citation statements)
references
References 86 publications
28
176
0
Order By: Relevance
“…Such methods may be particularly helpful in studying early clonal expansions in human tissues 93 . Recently, clonal expansions within morphologically normal tissues, resulting in somatically acquired mosaicisms, were identified throughout the body [4][5][6] .…”
Section: Somatic Genotyping In High-throughput Single-cellmentioning
confidence: 99%
“…Such methods may be particularly helpful in studying early clonal expansions in human tissues 93 . Recently, clonal expansions within morphologically normal tissues, resulting in somatically acquired mosaicisms, were identified throughout the body [4][5][6] .…”
Section: Somatic Genotyping In High-throughput Single-cellmentioning
confidence: 99%
“…DNA methylation (DNAm) refers to the addition of a methyl group (CH3) to a CpG dinucleotide (5'-C-phosphate-G-3'). In most cases, DNAm is associated with transcriptional repression via its effect on chromatin organization, and is thought to control a number of cellular properties, including differentiation [10], replication [11], Xinactivation [12], stress response [13], and genomic imprinting [14]. Initially, de novo methyltransferases establish methylation patterns that are necessary for organismal development [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, DNA methylation by DNMT3A or the Tet methylcytosine dioxygenase (TET2) was shown to regulate hematopoietic differentiation by controlling accessible binding sites for hematopoietic transcription factors including GATA1. 7 Moreover, very recent work has shown that precise DNA methylation patterning can control the binding and regulation of GATA1 activity. 8 Collectively, these findings suggest that the erythroleukemia-like phenotype in Nsd1 -/mice is probably the consequence of altered crosstalk between histone and DNA methylation.…”
mentioning
confidence: 99%